Development of Novel Rhodacyanine-Based Heat Shock Protein 70 Inhibitors - Chang, Chih-Shiang; Kumar, Vathan; Lee, Der-Yen; Chen, Yeh; Wu, Yu-Chieh; Gao, Jing-Yan; Chu, Po-Chen (Current Medicinal Chemistry, 2021)
Background: A growing body of evidence suggests that Hsp70, which is overexpressed in human breast tumors, plays a role in tumorigenesis and tumor progression in breast cancer as well as in its aggressive phenotypes. Hsp70 constitutes a potential therapeutic target in the treatment of this disease. Methods: We developed a new series of rhodacyanine-based Hsp70 inhibitors, represented by compounds 1 and 6, in which the cationic pyridin-1-ium or thiazol-3-ium ring of existing Hsp70 inhibitors (e.g., JG-40 and JG-98) was replaced by a corresponding benzo- fused N-heterocycle. Results: Several lines of evidence suggest that these benzo-fused derivatives may exert their antitumor activities, in part, by targeting Hsp70. These putative inhibitors displayed differential antiproliferative efficacy against breast cancer cells (IC50 as low as 0.25 μM) versus nontumorigenic MCF-10A breast epithelial cells (IC50 ≥ 5 μM). This was correlated with the corresponding Hsp70 expression levels. Using a protein refolding assay, we confirmed that these agents effectively inhibited the chaperone activity of Hsp70. Moreover, these inhibitors effectively suppressed the expression of well-known oncogenic client proteins of Hsp70’s, including FoxM1, HuR, and Akt, which paralleled their antiproliferative efficacy. Supporting the established role of Hsp70 in regulating protein refolding, these derivatives induced autophagy, as manifested by the conversion of LC3B-I to LC3B-II. Notably, these putative Hsp70 inhibitors did not cause a compensatory elevation in Hsp90 expression, contrasting with the previously reported effects of Hsp90 inhibitors on Hsp70 upregulation. Conclusion: Together with the finding that compounds 1 and 6 showed improved microsomal stability, these results suggest the translational potential of these putative Hsp70 inhibitors to foster new strategies for cancer therapy. However, whether these benzo-fused rhodacyanines act on kinases or other targets remains unclear. It is currently under investigation.
Keywords: Hsp70 inhibitors